Contribuição ao debate sobre políticas de proteção a margens de cursos d'água em áreas rurais no Brasil: impactos do novo código florestal - Wesley Ruas Silva (2014)
The riparian zones are important ecotones for environment and human population. In Brazil, they are protected by the Áreas de Preservação Permanente (APPs/Areas of Permanent Preservation), which in 2012 suffered major regulatory review. One of the items changed was the position of the APPs, which became the regular level instead of the highest level of the watercourse. Furthermore, in certain cases the APPs have had their sizes reduced. This research aimed to discuss the riparian zones protection policies in Brazil. Quantitative analysis was performed using data collected in basins of Minas Gerais (Brazil) and qualitative analyzes were performed by combining opinions of individuals involved with the theme. The data of 40 sites of the Três Marias Reservoir Watershed, 40 sites of the Nova Ponte Reservoir Watershed, and 40 sites of the Volta Grande Reservoir Watershed were obtained. 11 landowners were interviewed, 28 experts responded to the questionnaires and 2 experts were interviewed. 473 statements, 14 reports and votes, and 4 interviews were obtained from the group of political actors. The analyzes allowed the discussion of: (i) the position of the PPAs; (ii) the conflicts between the discourses of the actors involved; (iii) the environmental demands; (iv) the impasses between collective interests for environmental preservation and individual interests for land use; (v) the relationship between the doctrine of economic growth and the environmental protection policies in Brazil; (vi) the need to develop more effective policies to protect the riparian zones in Brazil. Among other things, the analyzes showed that there is not enough interaction between academic actors and political actors in the Brazilian legislative process. Furthermore, there is a need to establish accurately the position of the PPAs. In the conclusion this research brought a discussion about the alternatives to the current model of riparian zones protection policies in Brazil. In conclusion, this study raises the possibility of creating a democratic institutional structure specialized in the protection of riparian areas in Brazil.